Eksistensi Tafsir, Tasawuf dan Karya‘Abd al-Rauf As-Singkili di Nusantara - Nur Fadhilah Syam; Nasution, Muhammad Abdul Hakim; Siregar, Muhammad Rizky (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This paper aims to examine the person and role of 'Abd al-Rauf As-Singkili in the archipelago, especially in his existence through the study of tafsir, Sufism and books that have become references in carrying out worship in Muslim communities. This paper is categorised as a paper that uses a qualitative method by exploring themes related to the predetermined title, collecting data through relevant literature studies sourced from scientific journal studies that have been published both print and online. Furthermore, conducting data analysis stages with the stages of data reduction, data presentation and data verification. This paper argues that the existence of 'Abd al-Rauf As-Singkili still exists in various disciplines such as; tafsir, Sufism, hadith, fiqh which can be seen through his books, on the other hand, apart from being a mufassir, a carrier of the syattariyah tariqah he was also a jurist who was entrusted with being a qadhi during the Aceh kingdom.